Preparation of graft copolymer of chitosan-poly ortho-toluidine for antibacterial properties - Sama Sadat Hosseini; Seyed Hossein Hosseini; Abbas Hajizade (Heliyon, 2024)
The combination polymers or copolymers have new and combined properties and increase the efficiency of the new polymer. Biopolymers are biodegradable and can play the role of biocompatible and biodegradable in composite polymers. Therefore, poly ortho–toluidine was grafted on chitosan (Cs-g-POT) by chemical and electrochemical polymerization methods. Cs-g-POT was characterized by FTIR, UV–visible, and 1H NMR spectroscopy techniques. The thermal behaviors of the copolymer were investigated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The images of the surface of the copolymer obtained from imaging SEM confirm the successful attachment of POT on chitosan and indicate that the graft polymerization has been successfully performed with both methods. The percentage and efficiency of engraftment were carefully measured and reported. The electrical conductivity of Cs-g-POT was measured by the four-point method and the conductivity was 9.1 × 10−4 S/cm. The copolymer's antibacterial property was studied on Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa as a common bacterium in skin wounds. These studies were investigated using the disk diffusion and minimum inhibitory concentration (MIC) methods. In all tested concentrations the polymer could inhibit the growth of E. coli and P. aeruginosa significantly. However, it inhibited the growth of S. aureus in concentrations above 1 μg. Bacteria are adsorbed on the surface of the polymer by polar-polar and Van Der Waals interactions, where they undergo cell lysis by dopant and electron transfer, and eventually bacterial cell death. Due to its scaffolding properties, this polymer will have a very good use in tissue and bone repair as well as anti-cancer drugs.